Intramuscular lipoma of the tongue: an unusual intraoral entity / Kamariah Mohamed @ Awang, Abdul Halim Shibghatullah and Irfan Mohamad - Mohamed @ Awang, Kamariah; Shibghatullah, Abdul Halim; Mohamad, Irfan (Faculty of Medicine, 2024)
Lipomas are benign soft tissue neoplasms of mature adipose tissue. It is most commonly found in the torso or limbs. However, their incidence in the oral cavity is relatively rare. They are slowgrowing, painless mass and usually asymptomatic in nature. As they grow, they can interfere with the physiological processes in the surrounding area. We present a case of tongue lipoma in a 55-year-old man who had the painless mass for seven years. The mass was surgically excised. Histopathological examination confirmed the diagnosis.